Sisi lain kedokumentasian dan kepustakawanan Indonesia dalam sosok serta pemikiran Blasius Sudarsono - Christiani, Lydia (BACA: Jurnal Dokumentasi dan Informasi, 2023)
ABSTRACT This research is an individual life history. This research aims to examine in depth, systematically and critically the history of Blasius Sudarsono as a figure in the field of documentation and Indonesian librarianship, his original ideas and the socio-historical context of Blasius Sudarsono’s thoughts. Blasius Sudarsono’s loyalty in walking the path of librarianship for 50 years, as evidenced by his remaining productive in producing new works, even after entering retirement, is the object of study in this research. This research focuses on the thoughts of Blasius Sudarsono regarding the Universe of Documentation, the Basic Framework for Indonesian Librarianship (KDKI) and the Promise of Young Indonesian Librarians (JPMI). Blasius Sudarsono who never stops expressing his thoughts about Documentation and Indonesian Librarianship is the urgency of this research. This research was conducted using qualitative methods with a discourse analysis approach to the figure and thoughts of Blasius Sudarsono. Based on the results of this research, it was found that both in the realm of documentation in the form of the Universal Documentation concept, and in the realm of Indonesian librarianship in the form of the concept of the KDKI and the JPMI started from Blasius Sudarsono’s inner tendency to look for general documentation theory, which apparently also has a strong relationship in a unified universe with Indonesian librarianship. This also shows Blasius Sudarsono’s perspective of thinking which is out of the box and tends to present another side of documentation and Indonesian librarianship. Blasius Sudarsono’s thinking was produced through a triadic mindset. The results of Blasius Sudarsono’s thoughts are not meant to be the end of concept discovery, but are more intended to be a gateway to freedom of thought for the next generation in the field of documentation and Indonesian librarianship. ABSTRAK Penelitian ini merupakan studi tokoh. Penelitian ini bertujuan untuk mengkaji secara mendalam, sistematis dan kritis terkait sejarah sosok Blasius Sudarsono sebagai tokoh dalam bidang kedokumentasian dan kepustakawanan Indonesia, gagasan orisinal pemikirannya serta konteks sosio-historis pemikiran Blasius Sudarsono. Kesetiaan Blasius Sudarsono dalam menapaki jalan kepustakawanan selama 50 tahun yang dibuktikan dengan tetap produktif menghasilkan karya-karya baru, bahkan setelah memasuki masa purna tugas merupakan objek kajian dalam penelitian ini. Penelitan ini berfokus pada buah pemikiran Blasius Sudarsono tentang Semesta Dokumentasi, Kerangka Dasar Kepustakawanan Indonesia (KDKI) serta Janji Pustakawan Muda Indonesia (JPMI). Sosok Blasius Sudarsono yang tidak berhenti memancarkan pemikiran-pemikirannya tentang kedokumentasian dan kepustakawanan Indonesia menjadi urgensi dilakukannya penelitian ini. Penelitian ini dilakukan menggunakan metode kualitatif dengan pendekatan analisis diskursus terhadap sosok dan pemikiran Blasius Sudarsono. Berdasarkan hasil penelitian ini ditemukan bahwa baik pada ranah kedokumentasian dalam wujud konsep Semesta Dokumentasi, maupun pada ranah kepustakawanan Indonesia dalam wujud konsep KDKI dan JPMI berawal dari kecenderungan dari dalam diri Blasius Sudarsono untuk mencari general theory kedokumentasian, yang ternyata juga memiliki relasi yang kuat dalam sebuah kesatuan universum dengan kepustakawanan Indonesia. Hal ini sekaligus menunjukkan perspektif pemikiran Blasius Sudarsono yang out of the box dan cenderung menghadirkan sisi lain kedokumentasian dan kepustakawanan Indonesia. Pemikiran Blasius Sudarsono dihasilkan melalui pola pikir kebertigaan (triadic). Hasil pemikiran Blasius Sudarsono tidak bersifat sebagai akhir penemuan konsep, namun lebih dimaksudkan sebagai gerbang kemerdekaan berpikir bagi generasi penerus bidang kedokumentasian dan kepustakawanan Indonesia.